Guideline for IV infiltrations in pediatric patients. - Montgomery LA; Hanrahan K; Kottman K; Otto A; Barrett T; Hermiston B (Pediatric Nursing)
A large Midwestern tertiary care center used a multidisciplinary approach to develop an intravenous infiltration/extravasation guideline for pediatric patients, ages 0-18 years old, using the Iowa MODEL for research utilization. This infiltration clinical practice guideline included a site appearance staging tool, decision algorithm, research-based antidotes, and standard of care. The goal of the guideline was to prevent or minimize adverse occurrences for pediatric patients at risk for intravenous infiltrations. Quality assessment and improvement tracking suggested that there was an increased consistency in use of practice guideline interventions for and reporting of the infiltration event, a reduction in adverse patient outcomes, and potential cost savings.